(Nota n.º 4) Sôbre os nematódeos que parasitam o pessegueiro - Lordello, Luiz Gonzaga E.; Zamith, Adiel Paes Leme (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
This paper deals with galled peach roots from two localities in Brazil (Ouro Prêto and Piracicaba). Both samples were found attacked by Meloidogyne incognita acrita Chitwood, 1949. The material from Piracicaba also harboured two species of dagger nematodes (Xiphinema campinense Lordello, 1951, and X. krugi Lordello, 1955).